Employment Adjustments around Childbirth - Barbara Pertold-Gebicka; Filip Pertold; Nabanita Datta Gupta (Institute for the Study of Labor (IZA), 2016)
Using rich longitudinal register data from Denmark, we show that the allocation of mothers between the competitive private sector and the family-friendly public sector significantly changes around the birth of their first child. Specifically, mothers – post first childbirth – are increasingly switching from the private to the public sector and are also less likely to leave the public sector. The incidence of switching sectors can be partly explained by occupational characteristics, such as the convexity of pay and time pressure. In line with the compensating wage differential theory, we observe that the switch into the public sector is accompanied with a wage drop.
Keywords: J13; J16; J24; 330; motherhood; employment; sector switching; occupational characteristics